Per O. Hernæs: Slaves, Danes, and African Coast Society. The Danish Slave Trade from West Africa and Afro- Danish Relations on the Eighteenth- Century Gold Coast. (University of Trondheim, Department of History, 1995). 420 s. - Krieger, Martin (Historie/Jyske Samlinger, 1998)
-